How Trump and the Christian right saved LGBTI human rights a religious freedom mystery - Burack, Cynthia 1958-; Josephson, Jyl J. 1960- (Albany Suny Press, 2022)
"Traces the Trump administration's surprising support for LGBTI human rights abroad to Trump's indifference and the cynicism and political interests of Christian conservative elites"--
Includes bibliographical references and index
Keywords: Sexual Orientation -- Religious aspects -- Christianity; Gay rights -- Religious aspects -- Christianity; Sexual minorities -- Government policy -- United States -- History -- 21st century; Sexual minorities -- Civil rights; Sexual minorities -- Civil rights -- United States; Sexual Orientation -- Religious aspects -- Christianity; Gay rights -- Religious aspects -- Christianity; Sexual minorities -- Government policy -- United States -- History -- 21st century; United States -- Politics and government -- 2017-2021; United States -- Foreign relations -- 2017-2021